Transactions in doing design-based research for designing curriculum: a self-study. Issue 1 (2nd January 2019) - Isidro, Elizabeth
ABSTRACT: Design-based research (DBR) is an emerging methodology in teacher education research that researchers claim has strong potential in systematically designing and using instructional strategies and tools to develop, enact, and sustain effective learning environments. Studies have been conducted employing this methodology, but very little research has been made on the process of engaging in DBR for designing curriculum. Through a self-study, I found that using DBR as a model for creating curriculum draws from personal meaning-making, where I tapped on my own education, background, and experiences in literacy instruction to create curriculum. The other dimensions to the DBR process were more intangible and thus harder to negotiate. These included the political aspects, where decision-making was needed regarding course components. Keeping positive relationships with stakeholders was another challenging dimension in order to achieve a collectively meaningful curriculum. Finally, dispositions on literacy instruction also implied tension on the process since dispositions are not necessarily aligned with some DBR principles.